Selective hydroxyalkylation of phenol to bisphenol F over dodecatungstophosphoric acid (DTP) impregnated on fumed silica - Garade, Ajit C.; Kshirsagar, V. S.; Rode, C. V. (Applied Catalysis A-General, 2009)
The catalyst activity of various solid acids, such as fumed Silica (SiO(2)) dodecatungstophosphoric acid (DTP), DTP impregnated on SiO(2), amberlyst-15 and montmorillonite KSF/0, was studied for the hydroxyalkylation of phenol to bisphenol F. A well-dispersed DTP on SiO2 catalyst was prepared by the wet impregnation method. The effect of DTP loading on SiO(2) was also compared with bulk DTP and other solid acid catalysts. 20% DTP/SiO(2) catalyst gave the highest products yield of 34.2% and selectivity of 90.1% to bisphenol F, at 353 K and with a phenol-to-formaldehyde mole ratio of 5:1. Ammonia TPD studies of various catalysts showed that an appropriate combination of both strong and weak acid sites of DTP/SiO(2) Was mainly responsible, rather than only the stronger acidity of bulk DTP, for its highest catalytic activity and selectivity. The effect of various reaction parameters like mole ratio, catalyst concentration, temperature and reaction time on product yield and bisphenol F selectivity was also investigated. The catalyst recycle was established by catalyst activity testing. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Bisphenol F; Hydroxyalkylation; NH(3)-TPD; Reaction pathways; solid acid catalysts

Acidity tuning of montmorillonite K10 by impregnation with dodecatungstophosphoric acid and hydroxyalkylation of phenol - Garade, Ajit C.; Kshirsagar, V. S.; Mane, R. B.; Ghalwadkar, Ajay A.; Joshi, U. D.; Rode, C. V. (Applied Clay Science, 2010)
Acidity tuning of montmorillonite K10 (mont K10) was achieved by impregnating with dodecatungstophosphoric acid (DTP). The effect on the hydroxyalkylation of phenol was studied at 353 K with phenol to formaldehyde molar ratio of 5. The nature and strength of acid sites were determined by NH(3)-TPD measurement while the distribution of Brensted and Lewis acid sites expressed as B/L ratio, was determined by pyridine IR technique. Among various loadings of DTP (5-60%) studied for the hydroxyalkylation of phenol, 20% DTP/mont K10 showed the highest catalyst activity (90% selectivity to bisphenol F with 28% conversion of phenol). Both total concentration of acid sites and the distribution of acid sites in a high temperature region were required for the high bisphenol F selectivity. Our catalyst (20% DTP/Mont K10) could be recycled three times. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acidity tuning; Dodecatungstophosphoric acid/Montmorillonite K10; Hydroxyalkylation; Impregnation; Temperature programmed desorption

Structure-activity studies of dodecatungstophosphoric acid impregnated bentonite clay catalyst in hydroxyalkylation of p-cresol - Garade, Ajit C.; Kshirsagar, V. S.; Jha, Ajay; Rode, C. V. (Catalysis Communications, 2010)
Bentonite clay impregnated with dodecatungstophosphoric acid (20% DTP/BNT) showed an excellent activity, selectivity and stability [95% product yield with 94% selectivity to 2, 2'-methylenebis (4-methylphenol), DAM] for the hydroxyalkylation of p-cresol with formaldehyde at 353 K and for a mole ratio of 5. Ammonia-TPD results showed that an increase in total concentration of acid sites from 4.9 of parent bentonite to 11.6 micromoles per surface area NH(3) (mu molS(-1) NH(3)) of 20% DTP/BNT was due to a strong interaction of protons of bulk DTP with surface hydroxyl groups of BNT as evidenced by (31)P NMR studies. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: (31)P CPMAS NMR; Bentonite; Hydroxyalkylation; p-Cresol; surface modification